Disseminating complex primary outcome results from a community-randomised trial to Zambian communities: lessons learned using a community dialogue approach in the HPTN 071 (PopART) trial. Issue 11 (November 2022) - Simwinga, Musonda; Ndubani, Rhoda; Schaap, Albertus; Ziba, Daniel; Bwalya, Chiti; Belemu, Steve; Ngwenya, Fredrick; Bwalya, Justin; Shanaube, Kwame; Hoddinott, Graeme; White, Rhonda; Bock, Peter; et al.
Summary: The HPTN 071 (PopART) trial of universal HIV testing and treatment to reduce HIV incidence was conducted in nine communities in South Africa and 12 in Zambia. The trial's primary outcome results were complicated to explain. Dissemination of these complicated results in participating communities in Zambia was done using a community dialogue approach. The approach, which involved interactive activities and a gradual and systematic approach to discussion of results in each community, facilitated respect and inclusion of participants in the dissemination process. The use of local language, pictures, images, and familiar analogies enhanced comprehension of the findings and created a two-way communication process between researchers and participants. The dialogue approach enabled both groups to use community perspectives, lived experiences, and local socio-structural features to interpret the trial results. Further, community members reflected on what the results meant to them individually and collectively. Although this community dialogue was both productive and appreciated, making this community interpretation apparent across disciplines in key quantitative scientific outputs remained a challenge.